Governance theories and digitalisation: Four conjectures for the Mexican case - Francisco Porras (German Institute of Development and Sustainability (IDOS), 2025)
Governance theories offer a useful approach to policy by highlighting the need for multi-actor, multi-sectoral, and multi-level cooperation to deal with complex problems. Digitalisation, on the other hand, can be a means for managing networks, for helping to maintain the dynamics of meta-governance, and for generating problem-solving strategies based on knowledge exchange. Both seem to imply each other: governance requires tools to foster collaboration through the development of common understandings of problems, for which digitalisation can be instrumental. Effective digitalisation should foster governmental, social, and private steering towards public service, transparency, and the improvement of accountability. Digitalisation appears to require some basic conditions of governance related to fair access to services; beliefs and narratives that promote cooperation; processes of co-creation; and the interchange of information, as well as operative regulatory institutions. Governance and digitalisation together are fundamental for the management of complex policy problems. The aim of this Discussion Paper is theory advancement and refinement, linking assumptions about governance theories - particularly those resulting from the three waves of governance - to those of mainstream digitalisation literature. It formulates a research agenda to explore the possible mutual repercussions of those literature developments. The Discussion Paper is neither mainly descriptive nor prescriptive, but develops certain implications that stem from some fundamental problems of governance - defined as a process of multi-actor, multi-sector, multi-level cooperation - and digitalisation. The research agenda is presented in the form of conjectures relevant to the Mexican case, related to the roles, functions, and expected results of different actors dealing with governance problems within the context of increased digitalisation. The conjectures advance possible research areas related to the role of digitalisation in meta-governance carried out by governmental actors; in those of network cooperation maintained by academic institutions; in the improvement of problem-solving by non-governmental organisations; and in the possible co-creation of new knowledge through information-based interactions by the media.
Keywords: 320; Digitalisation; Latin America; Governance